Religion, federalism, and the struggle for public life : cases from Germany, India, and America - Everett, William Johnson (Oxford University Press, 1997)
Through a comparative study of India, Germany and the USA, this text examines the roles of religious traditions in the development of modern federal republicanism. It argues that a better comparative grasp of political and religious dynamics is essential to our understanding of the establishment, sustenance, and development of federal republican governance in both Western and non-Western cultures.
Keywords: Federal government -- Religious aspects -- Case studies.; Religion and state -- Germany -- History -- 20th century.; Religion and state -- United States.; Religion and state -- India -- History -- 20th century.; Germany -- Politics and government -- 1945-1990.; India -- Politics and government -- 1947-; United States -- Politics and government.; Germany -- Religion -- 20th century.; Religion et État -- Allemagne -- Histoire -- 20e siècle.; Religion et État -- États-Unis.; Religion et État -- Inde -- Histoire -- 20e siècle.; Allemagne -- Politique et gouvernement -- 1945-1990.; Inde -- Politique et gouvernement -- 1947-; États-Unis -- Politique et gouvernement.; Allemagne -- Religion -- 20e siècle.; POLITICAL SCIENCE -- Political Process -- Political Advocacy.; Federal government -- Religious aspects; Politics and government; Religion; Religion and state; Germany; India; United States; Föderalismus; Internationaler Vergleich; Staat; Verfassung; Deutschland; Indien; USA; Since 1900; Electronic books.; Case studies; History; Case studies.; Études de cas.